Laboratory and Field Evaluation of Insecticides against Fall Armyworm (Spodoptera frugiperda J. E. Smith) Larvae on Maize - Adhikari, Chiran; Dhungana, Swastika; Tiwari, Sundar; Thapa, Resham Bahadur; Nepane, Saraswati; Sharma, Sheela Devi (Journal of the Plant Protection Society, 2024)
Fall armyworm (Spodoptera frugiperda J. E. Smith) is a destructive pest that threatens maize production globally, including in Nepal. A laboratory leaf dip bioassay was conducted at Agriculture and Forestry University, Chitwan, to evaluate the efficacy of insecticides: chlorantraniliprole 18.5% SC, emamectin benzoate 5% SC, spinetoram 11.7% SC, spinosad 45% SC, azadirachtin 1500 ppm, malathion 50% EC, and chlorantraniliprole + lambda-cyhalothrin 0.15% ZC. Second-instar larvae were tested using a Completely Randomized Design with four replications. At the end of the experiment, 100 percent mortality was recorded for all treatments except malathion and azadirachtin. A field trial was conducted in 2022 on spring maize (Rampur Composite) in Chitwan, employing a Randomized Complete Block Design with eight treatments, including malathion, wood ash, soap solution, sawdust, azadirachtin, sugar solution, chlorantraniliprole + lambda-cyhalothrin, and water spray as a control, which were replicated three times. Applications were made twice (at 24 and 45 days after sowing), and data were collected before and after each spray. Based on the percentage of plant infestation with live larvae and foliar damage caused by larvae, chlorantraniliprole + lambdacyhalothrin was most effective, followed by azadirachtin. Local materials such as soap solution, wood ash, sawdust, and sugar solution also significantly reduced FAW damage. The study suggests that integrating chemical and local treatments offers a sustainable strategy for managing fall armyworm in maize.